Formation the system for assessing the economic security of enterprise in the agricultural sector - Pushak, Yaroslav; Lagodiienko, Volodymyr; Basiurkina, Nataliya; Nemchenko, Valerii; Lagodiienko, Nataliia (Business: Theory and Practice, 2021)
The complex of agroindustrial enterpriseis an extremely important branch of the national economy of any state. This area determines the level of food security, and can also be one of the powerful incentives for the growth of the entire economic system of the country. This is why it so important to ensure economic security of agroindustrial enterprise. The purpose of the article is to form the model for assessing the level of economic security of the agroindustrial enterprise. The subject of the study is economic security of the agroindustrial enterprise. It is proved that the effectiveness of anti-crisis measures substantially depends on information support, the formation of which at the proper level is possible when applying the developed model for assessing the level of economic security of the agroindustrial enterprise. The use in the model of quantitative and qualitative indicators can characterize the main parameters of the economic activity of the agroindustrial enterprise and allow to characterize the level of economic security. This model is based on data that were obtained during the assessment by experts who work in agroindustrial enterprises, which may not only be about professionalism, but also take into account the specifics of the studied area. As a result of obtaining one or another value of the integral indicator, the studied agro-industrial enterprise is recognized as requiring no revision of its own strategy for ensuring economic security. The generated model was experimentally applied at ten enterprises in Eastern Europe, in particular in countries such as Poland, the Czech Republic and Ukraine, to test its effectiveness. To define and substantiate our research, we applied the following general research methods: induction and deduction, comparison and systematization, synthesis and analysis, morphological analysis. The following methods are specific for our research: SAW methodology, in our work is designed to form a polyvariate decision-making model for assessing the level of economic security, as well as a method of expert evaluation, which are designed to form a list of necessary for the formation of the above model. The novelty of our research lies in the developed integrated indicator for assessing the level of economic security of agribusiness and its practical application.